Is the broadcast news media a he or she? a content analysis of the images of female news anchors and beat assignments of newscasters - Ucang, Regie I. 1993- (2014)
"Being the 'face' that personifies the mass media's function as a watch dog, the occupation of a newscaster is accompanied by a huge responsibility. This is why anchoring a news program requires a certain degree of expertise - alongside possessing the qualifications a news anchor must have. Such criteria and qualifications are not gender specific. However, several studies show that gender plays a significant role in determining credibility ratings. More so, gender stereotyping comes into play and presents man as tough, powerful, independent, vis-s-vis women who are depicted as passive, dependent, caregivers and often incompetent. Guided by theories on feminism, this study aims to unveil whether such social constructs of gender reflect on the beats assigned to news persons. Quantitative method was employed. In today's broadcast media, are male reporters automatically assigned to hard news and females to soft news? The researcher also looked into the female news anchors' physical appearance and how they present themselves in front of the camera. Through content analysis, the researcher analyzed two week's worth of primetime news episodes of the two leading media outfits in the country, GMA 7's 24 Oras and ABS-CBN's TV Patrol."